Agency and Motivation in Adulthood and Old Age. [article]. - Heckhausen, Jutta
This review addresses conceptual and empirical research about how individual agency and motivation influences development during adulthood and old age. The major life-span approaches to individual agency and developmental regulation are discussed, with a focus on the motivational theory of life-span development. Developmental agency unfolds through action cycles of pursuing long-term goals for optimal development. Individuals differ in their capacity to regulate their goal engagements effectively within the age-graded structure of opportunities and constraints in their life courses. We discuss a set of research examples about specific developmental challenges, such as transition to adulthood, biological aging, illness, and societal transformation, and show how individuals, as agents in their own development, navigate change for better or worse. We conclude with suggestions for future research. -- (from the author)